2022
DOI: 10.3390/pathogens11030292
|View full text |Cite
|
Sign up to set email alerts
|

Recent Strategies to Combat Biofilms Using Antimicrobial Agents and Therapeutic Approaches

Abstract: Biofilms are intricate bacterial assemblages that attach to diverse surfaces using an extracellular polymeric substance that protects them from the host immune system and conventional antibiotics. Biofilms cause chronic infections that result in millions of deaths around the world every year. Since the antibiotic tolerance mechanism in biofilm is different than that of the planktonic cells due to its multicellular structure, the currently available antibiotics are inadequate to treat biofilm-associated infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 172 publications
0
33
0
Order By: Relevance
“…Clinically, the long-term colonization of bacteria in humans causes chronic infections, mainly because the bacteria in biofilms are resistant to host immune responses and antibiotic therapy (Dufour et al, 2010). Research has shown that 65-80% of pathogenic infections in hospitals are associated with biofilms (Kumar et al, 2017;Shrestha et al, 2022). Although numerous antimicrobial agents are available for clinical use, these agents only inhibit infection symptoms and are unable to eradicate bacteria embedded in biofilms .…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, the long-term colonization of bacteria in humans causes chronic infections, mainly because the bacteria in biofilms are resistant to host immune responses and antibiotic therapy (Dufour et al, 2010). Research has shown that 65-80% of pathogenic infections in hospitals are associated with biofilms (Kumar et al, 2017;Shrestha et al, 2022). Although numerous antimicrobial agents are available for clinical use, these agents only inhibit infection symptoms and are unable to eradicate bacteria embedded in biofilms .…”
Section: Introductionmentioning
confidence: 99%
“…Implanted materials are highly susceptible to bacterial and fungal colonization and consequent infection [ 20 ]. These microorganisms are frequently opportunistic, taking advantage of the weakening of the body defenses at the implant surface–tissue interface, thereby attaching to tissues or implant surfaces, instigating biofilm formation and subsequent development of infection [ 13 , 21 ]. The development of biofilm causes tissue destruction, systemic dissemination of the pathogen and dysfunction of the implant/bone interface, resulting in the failure of implanted material [ 13 , 21 ].…”
Section: Implant-infecting Microorganismsmentioning
confidence: 99%
“…These microorganisms are frequently opportunistic, taking advantage of the weakening of the body defenses at the implant surface–tissue interface, thereby attaching to tissues or implant surfaces, instigating biofilm formation and subsequent development of infection [ 13 , 21 ]. The development of biofilm causes tissue destruction, systemic dissemination of the pathogen and dysfunction of the implant/bone interface, resulting in the failure of implanted material [ 13 , 21 ]. Additionally, the contaminated implant may serve as a reservoir for an infection of the surrounding tissue, where microorganisms may reside intracellularly [ 13 , 21 ].…”
Section: Implant-infecting Microorganismsmentioning
confidence: 99%
See 2 more Smart Citations